Emotional drivers of the vaccination hesitancy and refusal: A dataset from Slovakia - Magdalena Adamus; Vladimíra Čavojová; Eva Ballová Mikušková (Data in Brief, 2023)
The dataset comprises responses provided by 500 individuals (250 women) recruited by an external agency to be representative of the Slovak population concerning age and gender. Participants gave written consent to participate in the study by confirming that they are over 18 and have read all the information about the study before agreeing to participate in an online survey hosted on Qualtrics. Along with socio-demographic characteristics and vaccination hesitancy and refusal, the dataset contains variables that could explain variation in dependant variables: horizontal-vertical individualism-collectivism, consideration of future consequences, prosocial motivations, helplessness, and the sense of threat caused by vaccination but also the COVID-19 pandemic and the climate change. In the original paper, the authors performed correlational analysis and hierarchical regressions investigating antecedents of vaccination hesitancy and refusal. The data inform interventions aimed at boosting vaccination rates, particularly amongst highly sceptical societies such as Slovakia. Apart from investigating the relations between various forms of prosocial behaviour such as vaccination intentions and attitudes, helping behaviour during the pandemic, and pro-environmental behaviour, the dataset offers an opportunity to delve deeper into the drivers of various forms of socially beneficial behaviour. Ultimately, the data could help corroborate the existence of two new constructs of outward orientation (comprising future orientation, collectivism and prosocial motivations) and self-centred orientation (immediate orientation and individualism) that could be useful in explaining individual differences in prosocial intentions and behaviour.